Effect of proppant impingement on flow-induced corrosion of tubular steel super 13Cr via CFD and experiment - J.R. Cheng; N.S. Zhang; Y.P. Cao; Z. Li; Y.H. Dou (Egyptian Journal of Petroleum)
Data from a standard laboratory test including open-circuit potential (OCP) and current density monitoring is used to study the effect of fracturing proppant impingement on corrosion of tubular steel. A solid-liquid flow simulation is performed to obtain some parameters of particle movement and oxygen mass transfer near the metal surface. The results show that the electrochemical reaction includes passivation, activation and repassivation during a particle impact on the metal surface. Once the metal surface is in the activated state, the potential and anode current density is controlled by the oxygen concentration in the boundary layer and repassivation rate of metal surface. The increase of particle impact velocity accelerates the transmission of corrosion reactants and creates deeper impact craters on metal surface, resulting in the increase of current density. Meanwhile, the high speed particle impingement causes some platelets and extruding lips and thus weakens the surface corrosion resistance of stainless steel. Keywords: Tubular steel, Particle impingement, Flow-induced corrosion, Passive films, Repassivation